2018
DOI: 10.1002/pd.5228
|View full text |Cite
|
Sign up to set email alerts
|

What is the real “price” of more prenatal screening and fewer diagnostic procedures? Costs and trade‐offs in the genomic era

Abstract: Any screening approach, including with cell-free DNA, will have an inferior detection rate compared with 100% diagnostic testing with chromosomal microarrays. Cell-free DNA-based screening, however, should not be seen as a threat to informed choice or maximising the benefits of diagnostic testing. Screening methods have become so much better that more women are now comfortable relying on such screening and do not need the certainty of a diagnostic test. This has not lead to a decline in detection of fetal chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…NIPT cannot replace the prenatal diagnosis (CVS or amniocentesis) given the accuracy and wide detectable spectrum with the development of next generation sequencing (NGS) 46 . The importance of prenatal diagnosis has been emphasized by professional guidelines worldwide, and offered as an option for general pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…NIPT cannot replace the prenatal diagnosis (CVS or amniocentesis) given the accuracy and wide detectable spectrum with the development of next generation sequencing (NGS) 46 . The importance of prenatal diagnosis has been emphasized by professional guidelines worldwide, and offered as an option for general pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this decline in invasive procedures has not been associated with a decline in the detection of major chromosome abnormalities. Population‐based data showed that the diagnostic yield of amniocentesis and chorionic villus sampling actually increased during this period 96 . However, at least in Australia, the rate of invasive procedures appears to have plateaued in recent years, reaching a steady state of approximately 2% of births 97…”
Section: A Decade Of Invasive Proceduresmentioning
confidence: 99%
“…Population-based data showed that the diagnostic yield of amniocentesis and chorionic villus sampling actually increased during this period. 96 However, at least in Australia, the rate of invasive procedures appears to have plateaued in recent years, reaching a steady state of approximately 2% of births. 97 In 2010, NIPT was being conceptualised primarily as a screening test for trisomy 21.…”
Section: A Decade Of Invasive Proceduresmentioning
confidence: 99%
See 2 more Smart Citations